Pelos vapores e trens, do hipódromo ao stadium: esporte e lazer em Feira de Santana-BA (1875-1922) - Fábio Santana Nunes (2021)
We aimed to identify and analyze the public spectacles developed in the city of Feira de Santana, such as the theatre, the circus, the bull racing and the sports, as well as their organization methods, characters, perfomance locals, press representation methods, frequency of occurrence, participanting audiance and promoting institutions. We also intended to understand the reciprocal relationships between leisure and a wider social context, in particular, means of transport, urbanization and economic development. The time frame considered in the study comprises the late nineteenth century and the beginning of the twentieth. It is a Documentary Research, based mainly on newspapers and magazines published at the time in the studied city and other regions; works by memorialists and travelers; statistical reports and yearbooks; articles, dissertations and theses about the city. The results show that the theatre spectacles, bull racing, role-plays, horse racing, and soccer games took place in a period far from the urban growth and industrialization in the city of Feira de Santana. The functions largely used the only theater in the city, the Sant’Anna Theater, in addition to using the hippodrome from the Jockey Club of the city, the Leolindo Ramos Stadium, and large places like the Dr. Remédios Monteiro square and the Campo do Gado. The characters, institutions and cultural exchange between cultural practices, entities and other regions are highlighted. The transportation modes were important for the interiorization of the entertainment, connecting the Sertão of Bahia, specifically Feira de Santana to regions of the Recôncavo of Bahia, Salvador and other places of the world through the steamboat and by train, contributing to the offer of marketable leisure activities.